2013
DOI: 10.1371/journal.pone.0081607
|View full text |Cite
|
Sign up to set email alerts
|

Differential Haemoparasite Intensity between Black Sparrowhawk (Accipiter melanoleucus) Morphs Suggests an Adaptive Function for Polymorphism

Abstract: Recent research suggests that genes coding for melanin based colouration may have pleiotropic properties, in particular conveying raised immune function. Thus adaptive function of polymorphism may be associated with parasite resistance. The black sparrowhawk Accipiter melanoleucus is a polymorphic raptor with two morphs. Over most of its range the light morph is commonest, however within the recently colonised Western Cape of South Africa the dark morph predominates. The species breeds in winter throughout Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…) or parasite exposure (Lei et al . ). It is therefore logical that parental morphs could strongly influence both survival and recruitment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) or parasite exposure (Lei et al . ). It is therefore logical that parental morphs could strongly influence both survival and recruitment.…”
Section: Discussionmentioning
confidence: 97%
“…Parental morph was the other key variable. Numerous studies have shown differential life-history traits in melanin-based polymorphic species, which has led to the hypothesis that different morphs may be adapted to different environments, that may vary, for example in food abundance, social interactions (Roulin 2004b), weather conditions (Karell et al 2011) or parasite exposure (Lei et al 2013). It is therefore logical that parental morphs could strongly influence both survival and recruitment.…”
Section: Timing Of Breeding and Morph-specific Survival And Recruitmentmentioning
confidence: 99%
“…Several studies have indeed found correlations between melanin pigmentation and immune responses in wild vertebrates as a possible consequence of the POMC pleiotropy. However, the precise molecular link to the humoral response is so far unknown and the documented patterns are, at least partially, contradictory (Gangoso et al 2011(Gangoso et al , 2015Jacquin et al 2011Jacquin et al , 2013Lei et al 2013;Roulin et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The most conspicuous coloration trait in male pied flycatchers is the melanin‐based dorsal coloration that varies from completely brown to black (Drost, ; Lundberg & Alatalo, ). Melanin coloration is often linked with reproduction (Meunier et al ., ), stress sensitivity (Almasi et al ., ), parasite resistance (Lei et al ., ), and the costs of parasite infections (Karell et al ., ). Several studies have found context‐dependent selection on melanin‐based coloration (Roulin et al ., ; Dreiss et al ., ; Karell et al ., ; Dreiss et al ., ).…”
Section: Introductionmentioning
confidence: 99%